Corporate Income Taxes Around the World - A Survey on Forward-looking Tax Measures and Two Applications - Elias Steinmüller; Georg U. Thunecke; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2018)
This study provides a survey on corporate taxes around the world. Our analysis has three main objectives. First, we collect tax data and calculate (forward-looking) effective tax measures for a large sample of countries and recent years. We particularly describe how these measures vary over time and across countries. Second, we augment the country-level information with firm- and industry-level data (providing weights for financial structure and asset composition) to contrast statutory measures at the level of countries with measures accounting for firm- and industry-specific weights. Third, we utilize our new data to (i) estimate Laffer-Curves, i.e., the relationship between statutory tax rate and tax revenue, based on non-parametric as well as parametric specifications; (ii) examine how taxes affect investment in fixed assets at the level of firms. As for the latter, our preferred specification, in which we use a firm-specific effective marginal tax rate to capture tax incentives, suggests an elasticity of -0.33.
Keywords: H25; H21; F23; F61; 330; corporate taxes; depreciation allowances; effective marginal (average) tax rates; Laffer-Curve; investment responses